Analysis of the Science Assessment Items Using Scientific Literacy Competencies - Saiful Millah; Bibin Rubini; Indarini Dwi Pursitasari (Gagasan Pendidikan Indonesia, 2021)
This research aimed to analyze the science assessment in Junior High Schools in Tangerang Selatan City using scientific literacy competencies. This study used a descriptive method by collecting questions for the final semester assessment from four schools in Tangerang Selatan City, Indonesia which were determined by random sampling. A total of 180 science item test from four schools in Tangerang Selatan City, Indonesia were analyzed using scientific literacy competency indicators contained in the 2018 PISA framework. The results showed that only a small proportion (7.22%) of the items contained scientific literacy competencies. The items used tend to directly ask students' mastery of concepts and do not present data/information that students need to investigate on the items. Most of the questions presented are in the form of concept/definitions so that it does not require students to think at high levels, especially at the reasoning stage.